TELAAH KRITIS NILAI EDUKATIF KELONG MAKASSAR - Lukman (Jurnal Riset Guru Indonesia, 2023)
This research aims to identify and describe the form of educational values contained in Makassar "kelong" and the relevance of educational values in today's life. This research is designed using descriptive design, this research is not limited to data collection only, but includes analysis and interpretation. The research results in this study are in the form of data quotations that contain educational values in literary works. The results of this study show that the form of educational value in Makassar "kelong" recorded in lontarak is a reflection of the mindset and behavior of the Makassar people since centuries ago. Makassar "kelong" which is considered to have educational value can provide teaching and advice both to their children and to other people. The educational value can be found in the form of moral teachings, religious teachings, and others. "Kelong" which contains teachings or educational values related to moral, religious, and socio-cultural teachings has become a valuable asset for the development of Makassar literature. In addition, Makassar "kelong" has become philosophical (teachings for the people of Makassar) which needs to be appreciated by readers and listeners. Although lately many have ignored it. Based on the results of data analysis, the researcher hopes that Makassar "kelong" needs to be preserved because the teachings contained in it contain the local wisdom of the Makassar community. There should be a special institution created by the government that has the right to take care of regional arts that focuses more on revitalizing the artistic values and manners of the Makassarese people realized through "kelong".